Elbow loading during the backwards handspring: the influence of hand position - Needham, L.; Burton, S.; Farana, R.; Irwin, G. (ISBS Proceedings Archive (Michigan), 2017)
This study aims to investigate the influence of hand position on the musculoskeletal loading at the elbow during the back handspring in female artistic gymnastics. Six national level female gymnasts performed five back handspring trials with "inward", "parallel" and "outward" hand positions. Synchronised threedimensional kinematic and kinetic data were collected and inverse dynamics analysis performed to calculate elbow joint kinetics. Increased vertical and medio-lateral joint forces and higher medio-lateral moments at the elbow joint during the outward and parallel hand position may lead to increased injury risk. When using the outward and parallel hand positions, the elbow joint is exposed to increased joint kinetics and biophysical loading that may lead to an increased injury risk when performing the back handspring.